A new technical approach for real-time tensile strength testing of high-temperature granite based on micro-tensile testing technology - Li, Xianzhong; Tian, Yinnan; Li, Zhenhua; Heng, Shuai; Zhang, Xiaodong; Liu, Bing (International journal of mining science and technology, 2025)
The tensile strength of rocks under real-time high-temperatures is essential for enhanced geothermal system development. However, the complex occurrence and deep burial of hot dry rocks limit the quantity and quality of standard samples for mechanical testing. This paper compared the tensile strengths obtained from Brazilian splitting tests on standard samples (with a diameter of 50 mm and a thickness of 25 mm) and micro-tensile samples (with a diameter of 50 mm and a thickness of 25 mm) of two types of granites. A power-law size effect model was established between the two sets of data, validating the reliability of the testing method. Then, miniature Brazilian splitting under real-time high-temperature, combined with X-ray diffraction (XRD) revealed temperature-dependent strength variations and microstructural damage mechanisms. The results show that: (1) The comparison error between the tensile strength obtained by the fitting model and that of the measured standard samples was less than 6%. (2) In real-time high-temperature conditions, tensile strength of granite exhibited non-monotonic behavior, increasing below 300 °C before decreasing, with sharp declines at 400–500 °C and 600–700 °C. (3) Thermal damage stems from the differences in the high-temperature behavior of minerals, including dehydration, phase transformation, and differential expansion.